Frustration Intolerance, Self-Efficacy and Sleep Quality in Medical Students during Pandemic of Covid-19 - Sumaira Ayub; Zafar, Muhammad Shoaib; Kiran, Roop; Asif, Aftab (Journal of Pakistan Psychiatric Society, 2022)
Objective: To find out the relationship between frustration intolerance, self-efficacy and sleep quality in medical students and to determine the moderating role of self-efficacy in relationship between frustration intolerance and sleep quality in Medical Students Design: It was correlational study. Place and Duration: The study was conducted for a period of 4 months from November 2020 to January 2021 from students of different medical colleges of Lahore. Subjects and Methods: The sample comprised of 150 MBBS students from different medical, 126 (84%) were females and 24 (16%) were males. The age range of the participants was 18-26 years with mean age of 21.79 + 1.74 years old. Self-constructed demographic form, Frustration discomfort scale), Generalized Self efficacy Scale (Schwarzer & Jerusalem, 1995) and Sleep quality scales (Yi, Shin, and Shin, 2006) were also used to assess the sample. Data were collected online by employing non-probability convenient sampling strategy. Results: Frustration intolerance positively related with sleep quality indicating higher frustration linked with acute sleep problems, while self-efficacy showed negative relationship with sleep quality indicating higher self-efficacy decrease the sleep problems. so, results showed that self-efficacy moderated the relationship between frustration intolerance and sleep problems in medical students. Conclusion: This study identified high prevalence of frustration intolerance and poor sleep quality in medical students during pandemic of Covid-19, and highlighted the negative relationship of self-efficacy with frustration intolerance and sleep problems.